2009
DOI: 10.1111/j.1742-7843.2008.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Ethanolic Extract of Zingiber officinale Rhizome on the Development of Metabolic Syndrome in High‐Fat Diet‐Fed Rats

Abstract: Metabolic syndrome, including obesity, dyslipidaemia, hyperglycaemia and insulin resistance that predisposes type 2 diabetes is a major disease problem around the world and a plethora of herbal medicines are claimed to be effective in controlling these disorders. The rhizome of Zingiber officinale (Zingiberaceae) is commonly used as a spice in various foods and beverages. Apart from its other traditional medical uses, Z. officinale has been used to control diabetes and dyslipidaemia. In the present study, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
116
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(134 citation statements)
references
References 42 publications
12
116
2
4
Order By: Relevance
“…Islam and Choi, [11] reported no change in final body weight, fasting blood glucose, glycated hemoglobin and serum lipid profile in high-fat diet (22% fat) in STZ-induced diabetic rats after 4 weeks administration of freeze-dried ginger powder given at 2% of the diet but there was significant increase in serum insulin, though this did not result into a significant lowering of blood glucose. The report of Islam and Choi [11] was in conflict with that of Nammi et al, [12] who observed a significant reduction in body weight, fasting blood glucose, serum insulin, total cholesterol in high-fat diet fed rats which were given 400mg.kg body weight ethanol ginger extract. The variation in these reports could be as a result of differences in period of extracts' administration or differences in the form of ginger used.…”
Section: Introductioncontrasting
confidence: 53%
“…Islam and Choi, [11] reported no change in final body weight, fasting blood glucose, glycated hemoglobin and serum lipid profile in high-fat diet (22% fat) in STZ-induced diabetic rats after 4 weeks administration of freeze-dried ginger powder given at 2% of the diet but there was significant increase in serum insulin, though this did not result into a significant lowering of blood glucose. The report of Islam and Choi [11] was in conflict with that of Nammi et al, [12] who observed a significant reduction in body weight, fasting blood glucose, serum insulin, total cholesterol in high-fat diet fed rats which were given 400mg.kg body weight ethanol ginger extract. The variation in these reports could be as a result of differences in period of extracts' administration or differences in the form of ginger used.…”
Section: Introductioncontrasting
confidence: 53%
“…It is accepted that both hyperglycemia and dyslipidemia are important contributing factors to the development of atherosclerosis in type 2 diabetes [30] and hyperlipidemia represents a significant modifiable risk factor. In the HFD-treated rats [28] ginger extract effectively reduced the elevated levels of serum total cholesterol and LDL-cholesterol towards control levels, in addition to producing a marked reduction in elevated serum triglycerides, free fatty acids, and phospholipids. Similar results were found in another HFD study (60% fat and 10.6% carbohydrate), where Zingiber officinale extract (400 mg/kg for 6 weeks) reduced the enhanced triglyceride levels and showed a small but not significant decrease in hepatic cholesterol level [29].…”
Section: A High Fat Diet Modelmentioning
confidence: 99%
“…Related studies will be found in the original articles cited. [28]. In the earliest model examined [28] we investigated the effect of an ethanolic extract of ginger (which contained not less than 10% [6] Figure 1), at 1.56 mg/g, 0.24 mg/g, and 11.70 mg/g, respectively.…”
Section: Ginger In Animal Models Of Diabetes and Prediabetesmentioning
confidence: 99%
“…Também já foi avaliado in vivo o efeito do extrato etanólico do gengibre. Concluiu-se que o extrato administrado durante seis semanas, suprimiu o ganho de peso corporal e de glicose (48) . Ainda, outro estudo avaliou, durante três meses, o efeito da suplementação de gengibre em pacientes iranianos portadores de diabetes tipo 2.…”
Section: Discussionunclassified